Liposomes as biocompatible and smart delivery systems – the current state - Dymek, Michał; Sikora, Elżbieta (Advances in colloid and interface science, 2022)
Liposomes are self-assembled, closed spherical systems with a lipid bilayer, composed of i.a. one or more amphiphilic phospholipids, and widely used in the pharmaceutical, cosmetic and food industries. Whether composed of natural or synthetic lipids, liposomal vehicles are biocompatible, biodegradable, non-toxic and non-immunogenic carriers of active substances, both hydrophilic and hydrophobic by nature. Progress in liposome technology, modulation of the lipid composition, size and charge of the vesicle and modification of their surface has enabled the shift from conventional vesicles to "smart-generation" liposomes. Currently, liposomal vesicles are applied to improve the therapeutic effect of active substances and to provide the controlled release of drugs, thus prolonging the biological half-life or reducing toxicity of the actives. This paper reviews the recent process developments in liposomal systems, especially over the past decade. The methods of the systems preparation, characterisation and application are described. Additionally, methods of liposome surface modification and the mechanism of active substances delivery are outlined.Liposomes are self-assembled, closed spherical systems with a lipid bilayer, composed of i.a. one or more amphiphilic phospholipids, and widely used in the pharmaceutical, cosmetic and food industries. Whether composed of natural or synthetic lipids, liposomal vehicles are biocompatible, biodegradable, non-toxic and non-immunogenic carriers of active substances, both hydrophilic and hydrophobic by nature. Progress in liposome technology, modulation of the lipid composition, size and charge of the vesicle and modification of their surface has enabled the shift from conventional vesicles to "smart-generation" liposomes. Currently, liposomal vesicles are applied to improve the therapeutic effect of active substances and to provide the controlled release of drugs, thus prolonging the biological half-life or reducing toxicity of the actives. This paper reviews the recent process developments in liposomal systems, especially over the past decade. The methods of the systems preparation, characterisation and application are described. Additionally, methods of liposome surface modification and the mechanism of active substances delivery are outlined.